Забезпечення економічної стійкості малих будівельних підприємств – основа їх економічної безпеки - Вахович, І. В.; Молодід, О. О. (Ways to Improve Construction Efficiency, 2013)
Article is devoted to ensuring the economic sustainability of small construction enterprises in the context of bankruptcy prediction. Determination is made necessary characteristics of small construction companies, allowing them to finish on the state of economic security.